2007
DOI: 10.1038/nrc2148
|View full text |Cite
|
Sign up to set email alerts
|

The cofilin pathway in breast cancer invasion and metastasis

Abstract: Recent evidence indicates that metastatic capacity is an inherent feature of breast tumours and not a rare, late acquired event. This has led to new models of metastasis. The interpretation of expression-profiling data in the context of these new models has identified the cofilin pathway as a major determinant of metastasis. Recent studies indicate that the overall activity of the cofilin pathway, and not that of any single gene within the pathway, determines the invasive and metastatic phenotype of tumour cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
441
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(461 citation statements)
references
References 112 publications
(177 reference statements)
14
441
2
4
Order By: Relevance
“…Actin cytoskeleton participates in many cellular processes, including muscle contraction, cell motility and cell signaling. Cofilin 1 has a pivotal role in actin dynamics by modulating actin polymerization and depolymerization through its severing activity [33][34][35]. Here we find that depletion of NudC causes an accumulation of bundled stress fibers and inhibits cell spreading and lamellipodia formation (Figure 1), resembling the cellular phenotypes induced by cofilin 1 knockdown [29,30,33].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Actin cytoskeleton participates in many cellular processes, including muscle contraction, cell motility and cell signaling. Cofilin 1 has a pivotal role in actin dynamics by modulating actin polymerization and depolymerization through its severing activity [33][34][35]. Here we find that depletion of NudC causes an accumulation of bundled stress fibers and inhibits cell spreading and lamellipodia formation (Figure 1), resembling the cellular phenotypes induced by cofilin 1 knockdown [29,30,33].…”
Section: Discussionsupporting
confidence: 49%
“…Cofilin 1 has a pivotal role in actin dynamics by modulating actin polymerization and depolymerization through its severing activity [33][34][35]. Here we find that depletion of NudC causes an accumulation of bundled stress fibers and inhibits cell spreading and lamellipodia formation (Figure 1), resembling the cellular phenotypes induced by cofilin 1 knockdown [29,30,33]. Furthermore, our results show that NudC forms a complex with cofilin 1, colocalizes with cofilin 1 especially at the leading edge and influences the stability of cofilin 1 ( Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study, also in human aortic endothelial cells, revealed that Ang-(1–7) stimulated cofilin-1 expression [48]. Cofilin-1 is known to be involved in regulating actin filament dynamics and in cytokinesis [49] and has previously been implicated in cancer progression [50]. Ang-(1–7) stimulated G0/G1 arrest through a pathway involving cofilin 1, suggesting its importance for maintaining cell cycle homeostasis in response to Ang-(1–7) [48].…”
Section: Experimental Models Of Hypertensionmentioning
confidence: 99%
“…Unphosphorylated active cofilin associates with actin filaments in cell membrane protrusions where it drives actin dynamics by depolymerizing and severing ADP-bound actin filaments to regenerate the pool of In vivo metastasis 3/9 (33%) 7/9 (78%) actin monomers for new rounds of assembly at filament barbed ends 43 . Furthermore, the severing activity of cofilin is important for generation of the branched actin filament network that drives invasion and metastasis of cancer cells 44 .…”
Section: Identification Of Mtss1mentioning
confidence: 99%